1985
DOI: 10.1111/j.1365-2222.1985.tb02999.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine secretion from human skin slices induced by anti‐IgE and artificial secretagogues and the effects of sodium cromoglycate and salbutamol

Abstract: Human cutaneous mast cells show functional differences from their counterparts in other tissues. Following passive sensitization with T^ atopic serum for 30 min at 37 C human skin slices released histamine after challenge with anti-human IgE in a concentration dependent manner. Maximum release of 14 + 2";, was achieved with a 1/10 dilution of anti-IgE. Passive sensiti/ation with 10% atopic serum increased the secretory response to anti-IgE but histamine release was only concentration related over the entire l/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Histamine releasing cells of man, like those of the rat, show heterogeneity with respect to the action of SCG. Human basophil leucocytes (Church, 1982) and skin mast cells (Ting et al, 1983;Clegg et al, 1985) are refractory to its inhibitory effects. Immunological histamine release from human lung fragments is partially inhibited by SCG (Butchers et al, 1979;, but the variability of this model makes quantification of responses difficult .…”
Section: Introductionmentioning
confidence: 99%
“…Histamine releasing cells of man, like those of the rat, show heterogeneity with respect to the action of SCG. Human basophil leucocytes (Church, 1982) and skin mast cells (Ting et al, 1983;Clegg et al, 1985) are refractory to its inhibitory effects. Immunological histamine release from human lung fragments is partially inhibited by SCG (Butchers et al, 1979;, but the variability of this model makes quantification of responses difficult .…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that the responsiveness of IgE-mediated histamine release to modulation by sodium cromoglycate (SCG) differs markedly between human skin and lung mast cells [4], In mast cells dispersed from human lung tissue [6][7][8][9] and adenoids [10], SCG is a weak inhib itor of histamine and prostaglandin (PG) D2 release. On the other hand, in skin mast cells SCG has no inhibitory ef fect on IgE-dependent histamine release in in vitro [4,11,12] and in vivo studies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, experiments on human skin are conflicting. Three centres have shown that the drug does not prevent the release of histamine or other mediators from human skin, 23 from human skin slices 24 or from dispersed skin mast cells 25 . However, it has been shown to prevent the release of the inflammatory cytokine, tumour necrosis factor‐α, from mast cells in human skin 26 .…”
Section: Discussionmentioning
confidence: 99%